Peptidomic analysis in the discovery of therapeutically valuable peptides in amphibian skin secretions. (2nd December 2019) - Conlon, J. Michael; Mechkarska, Milena; Leprince, Jérôme
ABSTRACT: Introduction : The emergence of multidrug-resistant microorganisms has necessitated a search for new antimicrobial agents. Skin secretions of many frog species contain peptides that possess potent, broad-spectrum antibacterial and antifungal activities and so show promise for development into anti-infective agents. Several such peptides also possess cytokine-mediated anti-inflammatory properties and a range of anti-diabetic activities. Areas covered : A peptidomic approach, involving reversed-phase HPLC and MALDI mass spectrometry, to the comprehensive identification of peptides of potential therapeutic importance in frog skin secretions is described and its advantages over analyses involving bioassays discussed. Peptidomic studies relating to the characterization of peptides with demonstrated antimicrobial, anti-inflammatory and anti-diabetic properties in skin secretions of frogs belonging to the extensive Pipidae and Ranidae families are reviewed. Expert commentary : The initial promise of frog skin peptides as agents to treat infections produced by drug-resistant microorganisms has not been fulfilled although topical applications to treat skin diseases and a role in promoting wound healing remains a possibility. Future directions are more likely to involve the application of such peptides in the treatment of patients with sepsis and related inflammatory conditions and as a component of a therapeutic regime for Type 2 diabetes.